The Role of Social Capital in Human Investment: A Social Network Approach to College Success in the First Year - Berry, Todd (My University, 2008)
College and university leaders ask for tax and philanthropic support, arguing that their institutions promote economic progress through investment in human capital. Yet, despite Americans' pursuit of higher education in record numbers, graduation rates have remained stagnant for a generation due in large part to loss of students early in their college years. While higher education researchers continue to investigate student retention problems, they have so far ignored the role student networks can play in promoting academic success through the creation of social capital -- the idea that social contacts have value and can affect the productivity of groups and individuals. Todd Berry will illustrate how social network analysis can be used to define the elusive and much-abused concept of social capital so that it can be measured as a quantifiable variable. He also shares his research on the link between student-network social capital and academic success among first-year students at a Midwestern college.
Keywords: Access, Persistence, and Success